Corporate Governance as Determinants of Earnings Quality in Chinese Manufacturing Industry - ZHOU, Ge (2017)
This paper examines the relationship between corporate governance variables and earnings quality in the Chinese manufacturing industry. The research sets up two comparison groups: one state-owned enterprise group and the other private enterprise group. Then this research selects 234 manufacturing companies listed in Shanghai stock exchange market with complete data during 2011-2015. The empirical research finds that there are only three corporate governance variables (‘independirector’, LnCompensation’ and ‘shareholder concentration’) which are determinants on abnormal accruals in private enterprise group. These three corporate governance variables are negatively related to abnormal accruals. In state-owned enterprises, there is only one corporate governance variable (‘ROE ratio) determinant on abnormal accruals. The ROE ratio is positively related to abnormal accruals. This result suggests that the corporate governance is weaker in state-owned enterprises than it is in private enterprises.